Web Structure Mining: Exploring Hyperlinks and Algorithms for Information Retrieval - Kumar, R.; Singh, Ashutosh Kumar (Science Publication, 2010)
Problem statement: A study on hyperlink analysis and the algorithms used for link analysis in the Web Information retrieval was done. Approach: This research was initiated because of the dependability of search engines for information retrieval in the web. Understand the web structure mining and determine the importance of hyperlink in web information retrieval particularly using the Google Search engine. Hyperlink analysis was important methodology used by famous search engine Google to rank the pages. Results: The different algorithms used for link analysis like PageRank (PR), Weighted PageRank (WPR) and Hyperlink-Induced Topic Search (HITS) algorithms are discussed andcompared. PageRank algorithm was implemented using a Java program and the convergence of the PageRank values are shown in a chart form. Conclusion: This study was done basically to explore the link structure algorithms for ranking and compare those algorithms. The further research on this area will be problems facing PageRank algorithm and how to handle those problems.